Mulch: a boon for crop management - Kaur, Jagroop; Bons, Harsimrat K (Indian Farming, 2018)
Higher B:C ratio (1.29) was found under mulch over no mulch inkinnow. In another experiment on turmeric crop conducted at PunjabAgriculture University, Ludhiana, B:C ratio of 3.43 was observed under straw mulch compared to 1.03 with no mulch. During study it was also observed that plastic mulch is expensive, application of organic mulch is labour intensive and cumbersome and there is problem of rats and snakes.